Bringing psychotherapy research to life : understanding change through the work of leading clinical researchers - Castonguay, Louis Georges (American Psychological Association, 2010)
"This book brings together a large number of influential research programs that have changed the way we think about and practice psychotherapy. It presents the main findings derived by such scholarly and empirical endeavors in a way that, we hope, is conceptually meaningful and clinically relevant. These findings are also described in the context of the personal and professional journeys within which they originated; they are, in other words, historicized to some extent. We believe that such conceptualizing of scientific work can bring research to life and, in doing so, may help many clinicians to get back in touch with the excitement toward science that many of us felt as we first entered graduate school.